Qualitative Analysis of the Classical and Quantum Manakov Top - Sinitsyn, E.; Zhilinskii, B. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
Qualitative features of the Manakov top are discussed for the classical and quantum versions of the problem. Energy-momentum diagram for this integrable classical problem and quantum joint spectrum of two commuting observables for associated quantum problem are analyzed. It is demonstrated that the evolution of the specially chosen quantum cell through the joint quantum spectrum can be defined for paths which cross singular strata. The corresponding quantum monodromy transformation is introduced.